Sequential Vs Simultaneous Equilibria in A Differentiated Duopoly - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1996)
This paper tackles the issue of choosing roles in differentiated duopoly games. First, it is shown that the leader is not necessarily better off than in the simultaneous equilibrium. Second, it is proved that the sequential equilibria obtain only if both firms are better off under sequential play than under simultaneous play. Finally, a duopoly game under vertical differentiation and Bertrand competition is illustrated, where the price leader can indeed happen to be worse off than in the simultaneous equilibrium.
Keywords: 330